Implementasi Nilai-Nilai Pendidikan Islam Perspektif Ahlussunnah Wal-Jamaah dalam Pembentukan Akhlak Siswa di SMK Diponegoro, Depok, Sleman, Yogyakarta - Andrianto; Herman, Riki (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2022)
This study aims to describe the implementation of educational values ??from the perspective of ahlussunnah wal-jama'ah in Vocational High School (SMK) Diponegoro Depok Sleman Yogyakarta. The type of research used is qualitative research with Aswaja teachers as subjects and students at SMK Diponegoro Depok Sleman Yogyakarta. Data collection was carried out by observing, interviewing, documenting and triangulating. Data analysis was carried out through four stages, namely data clarification, data reduction, data interpretation and drawing conclusions. The results showed that: First, the basic concept of the value of Islamic education from the perspective of ahlussunnah wal-Jama'ah in shaping the morals of students at SMK Diponegoro Depok Yogyakarta includes honesty (As-shidqi), trustworthiness, loyalty and keeping promises (Al-amanah wal- wafa bi ahdi), fair (Al-is), help each other (At-ta'awun), consistent (Al-istiqomah), moderate and faithful (Attawasuthwa i'tidal), balanced (At-tawazun), tolerant (Tasamuh), and invite good, forbid doing evil (Amar ma'ruf nahi munkar). Second, the method of implementing student moral formation is through: school rules at school, students shaking hands with the teacher, praying when learning begins, praying in congregation, dhikr, tahlil and praying'. Third, implementing the formation of student morals by getting students used to shaking hands with teachers, parents and friends. Students are accustomed to praying, singing the Indonesia Raya song, selawat, and reciting the Koran before starting lessons. Students are familiarized with midday prayers and midday prayers at the mosque, and students are accustomed to reading and writing the Qur'an. 4). Fifth, the results of the application of the values ??of Islamic education from the perspective of ahlussunnah wal-jama'ah in the formation of student morals at Diponegoro Vocational School Depok Yogyakarta, students have good morals both in the school environment and in society, students are accustomed to doing sunnah worship such as Duha prayer, dhikr, tahlil and prayer, and students can worship according to the guidance of the sunnah of the Prophet Muhammad SAW.